Effects of transformational leadership on teachers' commitment in primary school in Kuching district / Mohammad Mathias Abdullah - Abdullah, Mohammad Mathias (2012)
This study aims to determine the level of transformational leadership among primary school headmaster in 3 schools in Kuching district in terms of idealized influence, individual consideration, intellectual stimulation and inspirational motivation and the organisational commitment of primary school teachers. The model of transformational leadership developed by Bums (1978), Bass (1985) and the organizational commitment model which was developed by Meyer and Allen (1991) served as the theoretical framework for the study. The transformational leadership classified into inspirational motivation intellectual stimulation and individual consideration. Sampling consisted of 150 teachers from three schools. Questionnaire is used for the survey and for collecting the data for the study. The instruments used in the study are "Multifactor Leadership Questionnaire" (MLQ). Cronbach alpha reliability value of .9575 obtained from the pilot study of 22 teachers. The questionnaires were collected and analyzed by using Statistical Package of Social Science (SPSS) 11.5 in terms of frequency and mean. The results showed that the level of transformational leadership practices of primary school headmaster in Kuching district is high and all the dimensions of transformational leadership were examined also showed higher mean values. The research indicated that the level of teacher’s organizational commitment was high too.